Pengaruh Budaya, Sosial, dan Pribadi terhadap Keputusan Pembelian Jamu Tradisional - Budi Hartono; Siti Nur Mukhlisoh (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The development of the times and increasingly modern technology accompanied by the emergence of modern products also makes everything required to be modern, including the minds of people who currently think that buying or consuming traditional herbal medicine is often called old-fashioned. Indonesia, which is known for its richness and diversity of tribes, cultures, and customs, there is no doubt that herbal medicine is one of the wealth of the archipelago that comes from the diversity of culture and local wisdom of the community as well as very high biodiversity. This study was conducted to determine the influence of culture, social, and personal on purchasing decisions of traditional herbal medicine. The method used in this study is a descriptive qualitative method with an ethnographic approach. The data used are primary data with data collection techniques carried out by observation and distributing questionnaires. The data was then analyzed by multiple linear regression using SPSS software. The results of the study prove that there is a significant influence between the Cultural (X1), Social (X2), and Personal (X3) variables on purchasing decisions (Y). Based on the results of the analysis that has been done, it can be seen that together cultural, social, and personal factors influence the purchasing decisions of traditional herbal medicine. Keywords: Culture, Personal, Social, Traditional Herbal Medicine, Purchase Decision